The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1177/1464884917700914
|View full text |Cite
|
Sign up to set email alerts
|

Military pollution in no war zone: The military representation in the local media

Abstract: This article analyses the local press’ representation of an experimental military activity located in Sardinia (Italy). We seek to assess the changes of the portrait of the military over a 57-year period, looking at the relevant narratives that have occurred in the local press. The authors’ perspective scrutinises the local print media as a key medium for understanding representations of the military and its activities. The adoption of frame analysis and the study of the frame effects highlight two main histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Following the CIA analysis, military facilities were built in poor, sparsely populated rural areas, with high unemployment and emigration rates. Previous research on the local media representation of military activities in Sardinia, has shown how the military was portrayed as a leading agent of modernity (Esu & Maddanu, 2017). Compensation for expropriated land was not systematically given, so some municipalities opened cases against the military and the state, especially when the occupied lands were governed by collective use legislation (Cacciarru, 2013).…”
Section: Sardinia Militarisation An Island Among Many Othersmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the CIA analysis, military facilities were built in poor, sparsely populated rural areas, with high unemployment and emigration rates. Previous research on the local media representation of military activities in Sardinia, has shown how the military was portrayed as a leading agent of modernity (Esu & Maddanu, 2017). Compensation for expropriated land was not systematically given, so some municipalities opened cases against the military and the state, especially when the occupied lands were governed by collective use legislation (Cacciarru, 2013).…”
Section: Sardinia Militarisation An Island Among Many Othersmentioning
confidence: 99%
“…Although the local population was quiescent, something began to shift public opinion on the island. The local newspaper, so supportive in building consensus on the military enterprise for more than twenty years (Esu & Maddanu, 2017), launched a warning campaign supporting the organisation of the first regional protest against military bases in 2014. This rally gathered political parties, regional deputies, associations, local committees and residents and mobilised the energy into a collective group.…”
Section: Sardinia Militarisation An Island Among Many Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…Activities range from the training of national and foreign units to testing missile prototypes and targets, from quality tests in cooperation with industries and organizations in the aerospace electronics sector and activities related to scientific research, testing, and experimenting of naval ammunition and medium-and long-range terrestrial, including the testing of missile systems, shooting practices, even interforce and for out-of-area operations. They have a significant negative impact [9,10] not only for the territory directly concerned, but also for the local communities, also given by a series of constraints (restriction on flying navigation, bathing, etc.) that they express themselves through easements-According to the Italian Civil Code (art.…”
Section: Introductionmentioning
confidence: 99%
“…This brief summary also includes Military Proving Ground (MPG), which have the following European location as shown in Figure 2, with a total of 284 MPG, mainly concentrated in the United Kingdom (55), the Netherlands (27), France and Germany (26 in each country), Switzerland (22), Spain (21), Italy and Poland (13 in each country). The multitude of activities that are carried out there 8 have a significant negative impact [9][10] not only for the territory directly concerned, but also for the local communities, also given by a series of constraints (interdiction of flight, navigation, bathing, etc.) that they express themselves through easements 9 , which vary according to the security that is required.…”
Section: Introductionmentioning
confidence: 99%